A Study on the Roles and Responsibilities of the Teaching Assistants to Promote Inclusive Education in a Mainstream School - Visma, Perathara (2016)
The government in United Arab Emirates recognizes the need to educate students with special needs and make efforts in promoting inclusive education in the country by implementing Federal Law 29/2006. This study researches the effects of having teaching assistants in classrooms to promote inclusive practices in a mainstream school. This qualitative study conducted in a private school in Dubai provides a snapshot on the roles, responsibilities, challenges and the effect of teaching assistants in aiding students with needs. Data collection was done by semi-structured interviews of teaching assistants, teachers and director of inclusion to obtain a rich contextual picture of the support provided. Further, it analyses and validates the efforts of the teaching assistant by conducting lesson observations and analysis of documents. The study reveals they had significant role in supporting students with needs in their varied roles of teaching, managing the classroom and facilitating interactions. However, for greater impact, certain areas need to be addressed in terms of clear role definition, training, collaboration and a system to monitor the quality of the support staff that paves way for student progress. Therefore, this study contributes by presenting information that can be pursued further for future empirical investigations to promote inclusive practices.